2014
DOI: 10.1021/ac500382x
|View full text |Cite
|
Sign up to set email alerts
|

Online Coupling of In-Tube Solid-Phase Microextraction with Direct Analysis in Real Time Mass Spectrometry for Rapid Determination of Triazine Herbicides in Water Using Carbon-Nanotubes-Incorporated Polymer Monolith

Abstract: Online coupling of in-tube solid phase microextraction (IT-SPME) with direct analysis in real time mass spectrometry (DART-MS) was realized for the first time and applied in the analysis of triazine herbicides in lake water and orange juice. We incorporated single-wall carbon nanotubes (SWNTs) into a polymer monolith containing methacrylic acid (MAA) and ethylene dimethacrylate (EDMA) to form a novel poly(methacrylic acid-co-ethylene dimethacrylate-co-single wall carbon nanotubes) (poly(MAA-EDMA-SWNT)) monolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(73 citation statements)
references
References 37 publications
0
73
0
Order By: Relevance
“…Compared with conventional mass spectrometry (MS) techniques, 14]. For instance, Liu's research team reported its application to the rapid determination of triazine herbicides in water [10]. Chernetsova and collaborators used DART MS to identify phenolic compounds in propolis [14].…”
mentioning
confidence: 99%
“…Compared with conventional mass spectrometry (MS) techniques, 14]. For instance, Liu's research team reported its application to the rapid determination of triazine herbicides in water [10]. Chernetsova and collaborators used DART MS to identify phenolic compounds in propolis [14].…”
mentioning
confidence: 99%
“…47 After direct extractions for 30 times, this coating still showed reproducible extraction efficiency. Recently, Wang and coworkers developed the interface of online coupling of in-tube solid-phase microextraction (IT-SPME) with DART-MS, as shown in Figure 3, 48 in wihch the single-wall carbon nanotubes incorporated monolith showed high affinity for six triazine herbicides. With the online combination of IT-SPME with DART-MS, the analytes desorbed from the monolith were directly ionized by DART and transferred into MS for detection, thus rapid determination was achieved.…”
Section: Sample Enrichment Before Dart-msmentioning
confidence: 99%
“…Furthermore, direct MS injection of complex samples may result in a high background noise, making qualitative and quantitative analyses of trace compounds very difficult. To reduce ionization suppression effect and matrix interferences a preliminary sample preparation procedure is performed, requiring time and skilled personnel, but this operation substantially reduces the number of substances that can be detected [22,24,25]. There is then an urgent need of reliable and high-throughput screening and/or quantification methods for compound determination in real samples, ranging from low to high contents and from low to high polarities.…”
Section: Introductionmentioning
confidence: 99%